The Analysis of Vocabulary Differences between Pontianak and Sandai Teochew Dialects - Jestin Hendriani; Lily Thamrin; Lusi (Syntax Literate, 2026)
This study examines the vocabulary differences between the Pontianak Teochew dialect and the Sandai Teochew dialect in West Kalimantan, Indonesia. The background of this research is based on the existence of linguistic variation among Teochew-speaking communities caused by migration history, language contact, and different social environments. The study aims to identify lexical similarities and differences between the two dialects and to explain the factors influencing these variations. This research applied a qualitative descriptive method through field observation, interviews, voice recordings, and vocabulary comparison. The data consisted of 1,300 lexical items collected from native Teochew speakers in Sandai and supported by secondary data from previous studies on Pontianak Teochew. The findings reveal that 88.15% of the vocabulary in both dialects is identical, while 11.85% differs. The differences are reflected in pronunciation, lexical borrowing, and environmentally influenced vocabulary formation. The Pontianak dialect is strongly influenced by Indonesian, Malay, Southern Min, and English, whereas the Sandai dialect shows stronger influence from Hakka and Mandarin. The study concludes that vocabulary variation between the two dialects is mainly influenced by differences in migration origin, language contact, and social environment. These findings contribute to dialectology and the preservation of Teochew linguistic heritage in Indonesia.